Project Based Learning di Kelas Terjemahan Bahasa Asing untuk Pendidikan Vokasional - Ahmad Muam (JLA (Jurnal Lingua Applicata), 2017)
The research aims to identify obstacles and possible challenges in deploying project based learning as learning method for translation course in vocational education.  Given that vocational education should shorten the gap between well-equipped skill of graduate with labor market demand, each courses offered are obliged to ensure that skill delivered in the course are practically in line with labor demand and are ready to use, including translation courses. The research adopted qualitative approach and putting case study method completed by interview and survey as method of data collection. The interview was intended to dig the faculty’s experience in facilitating translation courses in class within last one year period, particularly on its challenges and obstacles. Meantime, the survey was designed to absorb the learner’s perception and opinion towards the advantages of project based learning implementation. The respondent involved in the research are students of English program Vocational College Universitas Gadjah Mada who already taken translation 1 and 2 courses. Next,   The data are descriptively presented along with related supporting figures and tables. The research reveals that in the context of vocational education, translation teaching using project based learning offers a lot of advanteges to the students particularly in equipping them with proper undersntading on conceptual knowledge and its practical implementation in work place. However, its implementation hit some obstacles which could be derived as follow 1. Lack or time preparation and length of time to conduct the team project, 2. Lack of lecturer’s experience in delivering PBL in class.